Membangun Ekosistem Guru Cerdas di Era AI: Studi Kasus Pelatihan Generative AI di Desa Tantan - Rofiazka Fahmi Huda; Salman Jufri; Salman Hasani; Lely Mardiyanti; Lisa Rukmana (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Tantan Village, as part of the Integrated Laboratory Village (DLT) of Universitas Jambi, has great potential to develop human resources, particularly teachers who serve as the front line of educational transformation. However, most educators in this area still have limited digital literacy and minimal exposure to emerging technologies such as Artificial Intelligence (AI). This condition hinders the creation of adaptive, contextual, and innovative learning environments that align with the demands of the 21st century. This community service program was designed to enhance teachers’ capacity in utilizing Generative AI for educational purposes. The training employed a participatory and practice-based approach, consisting of three main stages: (1) Needs assessment and baseline survey, aimed at identifying teachers’ existing digital competencies and challenges in classroom practice; (2) Integrated training sessions, combining theoretical introductions to AI concepts with hands-on workshops using Generative AI tools to create teaching materials and automate administrative tasks; and (3) Community formation and mentoring, where participants collaboratively developed digital lesson plans and established a sustainable Digital Teacher Community of Tantan Village for peer learning and ongoing professional development. Data were collected through post-training questionnaires, observation sheets, and focus group discussions. The results indicate significant improvements in teachers’ digital literacy, confidence, and creativity in integrating AI tools into their teaching practice. Furthermore, the creation of a collaborative digital teacher network has fostered long-term engagement and innovation within the local education ecosystem. This program demonstrates that integrating Generative AI into teacher training can effectively bridge the digital literacy gap and accelerate the implementation of Smart Village initiatives by empowering and equipping educators with the technology they need.